Blood-pressure lowering in intermediate-risk persons without cardiovascular disease - Lonn, Eva M.; Bosch, Jackie; López‑Jaramillo, Patricio; Jun, Zhu; Lisheng, Liu; Pais, Prem; Md Aris, Mohd Aznan; Mohd Shah, Azarisman Shah; ., et. al (Massachusetts Medical Society, 2016)
Antihypertensive therapy reduces the risk of cardiovascular events among high-risk persons and among those with a systolic blood pressure of 160 mm Hg or higher,but its role in persons at intermediate risk and with lower blood pressure is unclear